Sources of resistance to Xanthomonas campestris pv. phaseoli from different geographical origins - Zapata Serrano, Mildred; Rodríguez, R.; Singh, Shree P. (1998)
Ten genotypes from the Vidac Negro 95 were found resistant to Xcp strains from Dominical Republic. These were: Dor 623, Ju-93-6, ICTA-JU-95-32, 45, 62, 66, 68, 70, 78 and 83. Two of these lines are resistant to Bean Golden Mosaic in Guatemala. A selected population of P. vulgaris genotype was evaluated with Xcp strains from Costa Rica, Guatemala, Nicaragua and Honduras. Best genotypes were Xan 309, G 17341 Vax 2, Vax 1, Great Northern; Sel 27 and W-BB-11. Differnces in races were determined between Xcp strains from the Caribbean (Dominicaan Republic) and Xcp strains from Central America (Costa Rica, Guatemala, Honduras and Nicaragua) inoculated on Phaseolus vulgaris genotypes.